Application of diagnostic and treatment criteria for common variable immunodeficiency disorder. (3rd March 2016) - Ameratunga, Rohan; Storey, Peter; Barker, Russell; Jordan, Anthony; Koopmans, Wikke; Woon, See-Tarn
ABSTRACT: Common variable immunodeficiency disorder (CVID) is the most frequent symptomatic primary immune deficiency disorder in adults. It probably comprises a spectrum of polygenic disorders, with hypogammaglobulinemia being the overarching feature. While the majority of patients with CVID can be identified with relative ease, a significant proportion can present with minimal symptoms in spite of profound laboratory abnormalities. Here we discuss three patients who were presented to the Auckland Hospital immunoglobulin treatment committee to determine if they qualified for immunoglobulin replacement. Two were asymptomatic with profound laboratory abnormalities while the third patient was severely ill with extensive bronchiectasis. The third patient had less severe laboratory abnormalities compared with the two asymptomatic patients. We have applied four sets of published diagnostic and treatment criteria to these patients to compare their clinical utility. We have chosen these patients from the broad phenotypic spectrum of CVID, as this often illustrates differences in diagnostic and treatment criteria.